Effect of hydroxyapatite concentration on high‐modulus composite for biodegradable bone‐fixation devices. Issue 7 (14th June 2016) - Heimbach, Bryant; Grassie, Kevin; Shaw, Montgomery T.; Olson, James R.; Wei, Mei
Abstract: There are over 3 million bone fractures in the United States annually; over 30% of which require internal mechanical fixation devices to aid in the healing process. The current standard material used is a metal plate that is implanted onto the bone. However, metal fixation devices have many disadvantages, namely stress shielding and metal ion leaching. This study aims to fix these problems of metal implants by making a completely biodegradable material that will have a high modulus and exhibit great toughness. To accomplish this, long‐fiber poly‐l ‐lactic acid (PLLA) was utilized in combination with a matrix composed of polycaprolactone (PCL) and hydroxyapatite (HA) nano‐rods. Through single fibril tensile tests, it was found that the PLLA fibers have a Young's modulus of 8.09 GPa. Synthesized HA nanorods have dimensions in the nanometer range with an aspect ratio over 6. By dip coating PLLA fibers in a suspension of PCL and HA and hot pressing the resulting coated fibers, dense fiber‐reinforced samples were made having a flexural modulus up to 9.2 GPa and a flexural strength up to 187 MPa. The flexural modulus of cortical bone ranges from 7 to 25 GPa, so the modulus of the composite material falls into the range of bone. The typical flextural strength of bone is 130 MPa, and the samples here greatly exceed that with a strength of 187 MPa. After mechanical testing to failure the samples retained their shape, showing toughness with no catastrophic failure, indicating the possibility for use as a fixation material. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1963–1971, 2017.